2011
DOI: 10.1007/s13197-010-0215-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of modified atmosphere packaging on quality of ‘Alphonso’ Mangoes

Abstract: Postharvest quality of Alphonso mangoes (Mangifera indica L) is vital to ensure proper ripening and good quality. 500 g mature green mangoes, were subjected to three pre-packaging hot water dips (20, 30 & 40°C) for 40 min, two packaging films (OPP unperforated and perforated), using three levels of gas concentrations of 25,50 and 75% v/v CO 2 treatments (balance N 2 ) and stored at 10°C for 21 days. During the storage period headspace gas composition, weight loss, ascorbic acid, pulp firmness, external fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 42 publications
4
12
0
Order By: Relevance
“…Effect of temperature, diameter and length of diffusion channel on PLW was found statistically significant (p≤0.05). The results obtained from this study were in conformation with the results reported by other authors (Kudachikar et al, 2011;Ramayya et al, 2012;Vunnam et al, 2014).…”
Section: Physiological Loss In Weightsupporting
confidence: 92%
See 1 more Smart Citation
“…Effect of temperature, diameter and length of diffusion channel on PLW was found statistically significant (p≤0.05). The results obtained from this study were in conformation with the results reported by other authors (Kudachikar et al, 2011;Ramayya et al, 2012;Vunnam et al, 2014).…”
Section: Physiological Loss In Weightsupporting
confidence: 92%
“…This atmosphere can potentially reduce the rate of respiration of the produce (Zagory and Kader, 1988;Mahajan and Goswami, 2001;Fonseca et al, 2002). Several researchers (Klieber et al, 1996;Sozzi et al, 1999;Akbudak and Eris, 2004;Kudachikar et al, 2011;Ramayya et al, 2012;Majidi et al, 2014;Vunnam et al, 2014) have been conducted experiments on enhancing the shelf life of various fruits by altering the gas compositions. Polymeric films, used as packaging materials for modified atmosphere packaging (MAP) are limited to gas permeability.…”
Section: Introductionmentioning
confidence: 99%
“…Retardation of ripening and associated physiological and biochemical changes (transpiration, respiration, ethylene production, softening and compositional changes) have been achieved by the application of controlled atmosphere (CA), modified atmosphere (MA) or modified atmosphere packaging (MAP) (Kader 1986;Leshuk and Saltveit 1990;Kanellis et al 1993;Kader and Saltveit 2003a, b;Yahia 2009;Kanellis et al 2009;Mangaraj and Goswami 2009). These approaches have in fact become the established methods for extending the postharvest-life of fruits (Yahia 2009;Mangaraj and Goswami 2009;Kader 2009;Sharma et al 2011;Ramayya et al 2011). It has been observed that CA, MA and MAP basically modify the internal gaseous atmosphere of the fruits in favour of low O 2 to CO 2 ratio Elyatem et al 1994;Klieber et al 1996;Baldwin et al 1999;Amarante et al 2001;Gil et al 2002;Kader 2009;Berry and Sargent 2009;Mangaraj and Goswami 2009;Kanellis et al 2009;Yahia 2009;Ramayya et al 2011;Nath et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These approaches have in fact become the established methods for extending the postharvest-life of fruits (Yahia 2009;Mangaraj and Goswami 2009;Kader 2009;Sharma et al 2011;Ramayya et al 2011). It has been observed that CA, MA and MAP basically modify the internal gaseous atmosphere of the fruits in favour of low O 2 to CO 2 ratio Elyatem et al 1994;Klieber et al 1996;Baldwin et al 1999;Amarante et al 2001;Gil et al 2002;Kader 2009;Berry and Sargent 2009;Mangaraj and Goswami 2009;Kanellis et al 2009;Yahia 2009;Ramayya et al 2011;Nath et al 2011). These methods also regulate ethylene production and its response (Scully and Horsham 2008;Yahia 2009;Mangaraj and Goswami 2009;Kanellis et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…2010) on "Kent" mangoes showed that cold storage at 10 o C combined with MAP maintained quality and prolonged the shelf life (to 6 weeks) compared to cold storage alone where the shelf life was extended for only 2-3 weeks. The shelf life of mango fruits was extended up to 21 days using MAP compared to the shorter shelf life of 12 day for fruits not subjected to MAP as observed by Ramayya et al (2012).…”
Section: Introductionmentioning
confidence: 77%